CT-Guided Pulsed Radiofrequency at Different Voltages in the Treatment of Postherpetic Neuralgia - Han, Zhenkai; Hong, Tao; Ding, Yuanyuan; Wang, Shimeng; Yao, Peng (Frontiers in Neuroscience, 2020)
Postherpetic neuralgia (PHN) is a form of long-lasting neuropathic pain that can severely affect patients’ quality of life. Pulsed radiofrequency (PRF) has been proven to be effective in treating PHN, but the optimal radiofrequency parameters are still not well defined. We treated PHN patients using CT-guided PRF at three different voltages to compare the efficacy and safety. Methods: This prospective cohort study included 109 patients with PHN involving the thoracic dermatome who were treated in the Department of Pain Management of Shengjing Hospital, China Medical University, from January 2017 to May 2019. They were all treated with PRF, and were divided into three groups based on the voltage used: group A (45 V), group B (55 V), and group C (65 V). We then compared visual analog scale (VAS) scores, 36-Item Short Form Health Survey (SF-36) scores, patient satisfaction, and risk of complications among these patients to evaluate treatment outcomes. Results: VAS scores decreased and SF-36 scores increased for all patients in the three groups at each post-operative time point (1 month, 3 months, 6 months, and 12 months; all P < 0.01). Pain relief, improvement in quality of life, and overall satisfaction were more significant for patients in group C than for those in groups A and B at the 3-, 6-, and 12-month follow-ups (all P < 0.05). And patients in group B had lower VAS scores and higher overall satisfaction levels than those in group A (both P < 0.01). A small number of patients from each group (n ≤ 3) experienced mild intraoperative and postoperative complications, which bore no relationship with group assignment (all P > 0.05). At post-operative day 3, patients in group C had skin numbness affecting a larger area than patients in the other two groups (both P < 0.05), but the differences were no longer statistically significant at day 30 after the operation. All patients experienced a drop in numbness area of more than 30% after surgery. Conclusion: Compared with PFR at 45 V and 55 V, PFR at 65 V had superior efficacy in treating PNH, with a favorable safety profile.